Abdominal Compartment Syndrome: Risk Factors, Diagnosis, and Current Therapy - Gina M. Luckianow; Matthew Ellis; Deborah Governale; Lewis J. Kaplan (Critical Care Research and Practice)
Abdominal compartment syndrome’s manifestations are difficult to definitively detect on physical examination alone. Therefore, objective criteria have been articulated that aid the bedside clinician in detecting intra-abdominal hypertension as well as the abdominal compartment syndrome to initiate prompt and potentially life-saving intervention. At-risk patient populations should be routinely monitored and tiered interventions should be undertaken as a team approach to management.